Seminoma in Undescended Intra Abdominal Testis: A Case Report - Haque, MM; Siddique, AB; Rabbani, ABMG; Quasem, MA; Rahman, AKMG; Rahman, MM (TAJ: Journal of Teachers Association, 2009)
A mass in the lower abdomen in a sexually active man with a cryptorchid testis strongly points towards the diagnosis of malignancy in the abdominal testis.1 The incidence of testicular tumor is 11 times more in inguinal testes and 50 times more in intra abdominal testes. 2 Normally, the testes, which are inside the abdomen during gestation, migrate into the scrotum by the time of birth. Occasionally, boys are born with testes that are still in the abdomen or in the groin, not having completed their journey to the scrotum. These undescended testes are at high risk of cancer and should be moved into the scrotum at an early age or removed entirely. doi: 10.3329/taj.v18i2.3194 TAJ 2005; 18(2): 131-133